Gentrification, Property Tax Limitation, and Displacement. Issue 1 (January 2018) - Martin, Isaac William; Beck, Kevin
Scholars have long argued that gentrification may displace long-term homeowners by causing their property taxes to increase, and policy makers, including the U.S. Supreme Court, have cited this argument as a justification for state laws that limit the increase of residential property taxes. We test the hypotheses that gentrification directly displaces homeowners by increasing their property taxes, and that property tax limitation protects residents of gentrifying neighborhoods from displacement, by merging the Panel Study of Income Dynamics with a decennial Census-tract-level measure of gentrification and a new data set on state-level property tax policy covering the period 1987 to 2009. We find some evidence that property tax pressure can trigger involuntary moves by homeowners, but no evidence that such displacement is more common in gentrifying neighborhoods than elsewhere, nor that property tax limitation protects long-term homeowners in gentrifying neighborhoods. We do find evidence that gentrification directly displaces renters.